IMPLEMENTATION OF SOCIOLOGY OF EDUCATION IN FORMATION OF CHARACTER THROUGH DISCIPLINE TRAINING - Kushariyati, Kushariyati; Nashrullah, Mochamad; Churrahman, Taufik (PT ANTIS INTERNATIONAL PUBLISHER, 2024)
Character education is a system that teaches character values ​​with elements of knowledge, awareness and action, as well as putting these values ​​into practice. One way to develop quality character or educate children about their character is to provide knowledge about how to behave according to expectations in everyday life and apply it in society. This characteristic behavior is certainly related to relationships with society. Since humans were born into this world, consciously or unconsciously, we have studied and understood social relationships, namely the relationships between humans in society. The research method in this article uses qualitative research: Literature Study, namely a data collection method by understanding and studying theories from various literature related to research. The aim of this research is to examine the sociology of education, the sociology of education as character formation through disciplinary habituation and implementation of disciplinary character formation.